UCC118 supplementation reduces exercise‐induced gastrointestinal permeability and remodels the gut microbiome in healthy humans. Issue 22 (23rd November 2019) - Axelrod, Christopher L.; Brennan, Connery J.; Cresci, Gail; Paul, Deborah; Hull, Michaela; Fealy, Ciarán E.; Kirwan, John P.
Abstract: Dysregulation of gut microbiota and intestinal barrier function has emerged as potential mechanisms underlying digestive diseases, yet targeted therapies are lacking The purpose of this investigation was to assess the efficacy of UCC118, a characterized probiotic strain, on exercise‐induced GI permeability in healthy humans. In a randomized, double‐blind, placebo‐controlled crossover study, seven healthy adults received 4 weeks of daily UCC118 or placebo supplementation. GI hyperpermeability was induced by strenuous treadmill running performed before and after each supplementation period. While running, participants ingested 5 g of lactulose, rhamnose, and sucrose. Urine was collected before, immediately after, and every hour for 5 h after exercise to assess GI permeability. Metagenomic sequencing was performed on fecal homogenates collected prior to exercise to identify changes in microbial diversity and taxon abundances. Inflammatory biomarkers were assessed from blood and fecal homogenates collected prior to and immediately following the cessation of exercise. Exercise significantly induced intestinal permeability of lactulose, rhamnose, and sucrose ( P < 0.001). UCC118 significantly reduced sucrose (Δ = −0.38 ± 0.13 vs. 1.69 ± 0.79; P < 0.05) recovery, with no substantial change in lactulose (Δ = −0.07 ± 0.23 vs. 0.35 ± 0.15; P = 0.16) or rhamnose (Δ = −0.06 ± 0.22 vs. 0.48 ± 0.28; P = 0.22). Taxonomic sequencing revealed 99 differentially regulated bacteria spanning 6 taxonomic ranks ( P < 0.05) after UCC118 supplementation. No differences in plasma IL‐6 or fecal zonulin were observed after UCC118 supplementation. The results described herein provide proof of principle that 4 weeks of UCC118 supplementation attenuated exercise‐induced intestinal hyperpermeability. Further research is warranted to investigate the as‐yet‐to‐be defined molecular processes of intestinal hyperpermeability and the effects of probiotic supplementation. Abstract : Dysregulation of gut microbiota and intestinal barrier function have emerged as potential mechanisms underlying digestive diseases, yet targeted therapies are lacking. In a randomized, double‐blind, placebo‐controlled crossover study, 7 healthy adults 30 received 4 weeks of daily UCC118 or placebo supplementation. UCC118 significantly reduced sucrose recovery. Taxonomic sequencing revealed 99 differentially regulated gut microbes by UCC118. The results herein provide proof of principle that UCC118 supplementation can reduce intestinal hyperpermeability.